Effects of assisted reproductive technology on gene expression in heart and spleen tissues of adult offspring mouse - Chen, Huanhuan; Zhang, Lei; Yue, Feng; Cui, Chenchen; Li, Yan; Zhang, Qingwen; Liang, Linlin; Meng, Li; Zhang, Cuilian (Frontiers in Endocrinology, 2023)
Assisted reproductive technology (ART) is an important part of reproductive medicine, whose possible effects on offspring’s health have drawn widespread attention in recent years. However, relevant studies are limited to postnatal short-term follow-up and lack of diverse sample sources analysis other than blood. In this study, a mouse model was used to explore the effects of ART on fetal development and gene expression in the organs of offspring in the adulthood using next-generation sequencing. The results showed that it caused abnormal expression in 1060 genes and 179 genes in the heart and spleen, respectively. Differentially expressed genes (DEGs) in the heart are mainly enriched in RNA synthesis and processing, and the cardiovascular system development also shows enrichment. STRING analysis identified Ccl2, Ptgs2, Rock1, Mapk14, Agt, and Wnt5a as the core interacting factors. DEGs in the spleen are significantly enriched in anti-infection and immune responses, which include the core factors Fos, Jun and Il1r2. Further exploration revealed the abnormal expression of 42 and 5 epigenetic modifiers in the heart and spleen, respectively. The expression of the imprinted genes Dhcr7, Igf2, Mest and Smoc1 decreased in the hearts of ART offspring, and the DNA methylation levels of Igf2- and Mest-imprinting control regions (ICRs) increased abnormally. Therefore, we concluded that, in the mouse model, ART can interfere with the gene expression pattern in the heart and spleen of the adult offspring and that these changes are related to the aberrant expression of epigenetic regulators.